Nutrient Intake and Dietary Practices of Elite Volleyball Athletes during the Competition Day - Janaka Prasanna Gamage; Angela De Silva (The Society of Aging and Physical Activity (SAPA), 2014)
Adequate quality and quantity of athletes' competition day diet is critically important for better performance and optimum recovery. The aim of this study was to evaluate the adequacy of nutrient intake and dietary practices of Sri Lankan national volleyball players during a day of a major competition. Dietary practices of 76 athletes (43 males and 33 females) were surveyed using 24-hour dietary recall method. Energy and macronutrient intakes were quantitatively assessed in relation to competition using a computerized nutrition analysis software and local food database. Questionnaire was used to examine supplement intake and fluid intake strategies. The results were compared with current nutrition recommendations for these athletes. Mean daily energy intakes were 2309+365 kcal (30.9+5.7 kcal.kg-1.body weight) in male and 1829+383 kcal (30.8+6.8 kcal.kg-1.body weight) in female athletes. These intake values were 31% and 18% lower than recommended daily energy intake for active Sri Lankan male and female adults, respectively. Daily carbohydrate and protein intakes of all athletes were 5.6+1.0 g.kg-1.day-1 and 0.91+0.37 g.kg-1.day-1, respectively, lower than the recommendations. Total energy, carbohydrate, and protein intake of female athletes were significantly lower than those of males (p<0.05). Frequency of snack intake and calorie content of snacks and main meals in the pre-competition period was sub-optimal. Nutrient intake and dietary practices of national level volleyball players during competition days are sub-optimal and do not meet the current nutrition recommendations. According to the results, it is recommended that athletes use nutrition counselling and strategies for optimizing dietary practices during the competition days.